PERAN PENGELUARAN PEMERINTAH, POPULASI, DAN KUALITAS SDM DALAM MENURUNKAN TINGKAT PENGANGGURAN DI DAERAH BERKEMBANG - Andi Baso Siswadarma; Fatmawati Fatmawati; Fakhrul Indra Hermansyah (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
A high rate of unemployment has existed in Barru Regency, a developing region, for nearly twenty years. The purpose of this study is to examine how population growth, government spending, and the quality of human resources all contribute to a lower unemployment rate. The time-series data, which spans the years 2000–2022, was obtained from BPS-Statistics Indonesia and Barru. This study employs a quantitative, econometric methodology with an emphasis on ordinary least squares. The findings of this study demonstrate that the government must be committed to developing strategic policies that prioritize enhancing human quality via health and education in order to lower the unemployment rate. In order to address the elevated rate of unemployment, the government must direct funds towards profitable economic ventures and maintain population control.Â Keywords: Developing Region, Government Expenditure, Human Development Index, Population, UnemploymentÂ